PENGARUH HARGA PSIKOLOGIS TERHADAP ETIKA BISNIS - SRI RAMADHAN (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Article examines the issue of psychological pricing. The formulation of the research is whether the psychological price already meet the criteria for a fair price and not contrary to business ethics in Islam. Research is a research library. The study is qualitative. The research approach is hermeneutic data analysis technique used is descriptive-analysis-critical. The study's findings are a) The relationship between ethics and business is something that cannot be separated from each other, and b) pricing of psychological conflict with Islamic business ethics.